Impacto da fibrilação atrial no prognóstico da insuficiência cardíaca crônica sistólica secundária à cardiomiopatia da doença de chagas - Ardito, Sabrina Queiroz (2018)
Chagas disease is caused by the parasite Trypanosoma cruzi. It is a chronic, systemic disease, which affects about 6 million people in Latin America and 30-40% has cardiomyopathy secondary to this disease. In the vast majority of cases, the main cause of death is related to the final stages of chronic heart failure. Chagas disease has become a growing health problem in non-endemic areas due to migration. Objective: To evaluate the impact of atrial fibrillation on the prognosis of chronic systolic heart failure secondary to Chagas cardiomyopathy. Material and Methods: About 234 patients routinely followed at the Cardiomyopathy Outpatient Service of Hospital de Base of São José do Rio Preto Medical School in the SUS, from January 2000, to December 2010, with the diagnosis of chronic heart failure secondary to Chagas cardiomyopathy were included in the study. A Cox proportional hazard model was used to detect independent predictors of all-cause mortality in the studied population. A survival curve was built for patients with and without atrial fibrillation. In all the circumstances, p value <0.05 was considered statistically significant. Results: Atrial fibrillation was observed in 63 patients (26.9%). In a cox proportional hazard model analysis, beta-blocker therapy ( Hazard Ratio=0.381; 95% Confidence Interval 0.257 to 0.563, p value <0.001), use of metoprolol succinate (Hazard Ratio=0.382; 95% Confidence Interval 0.170 to 0.855, p value=0.019), use of Losartan (Hazard Ratio=0.611; 95% Confidence Interval 0.380 to 0.981, p value =0.041), and left systolic ventricular diameter (Hazard Ratio=1.042; 95% Confidence Interval 1.021 to 1.063, p value <0.001) were determined independent predictors of all-cause mortality. Survival probability at 12, 24, 36, 48 and 60 months was 80%, 65%, 56%, 44% and 37%, respectively, in patients without atrial fibrillation, and 76%, 58%, 48%, 41% and 32% in patients with atrial fibrillation, (p=0.393). Conclusion: Atrial fibrillation has no prognostic significance in patients with chronic systolic heart failure secondary to Chagas Cardiomyopathy.